Development of a hoisting safety risk framework based on the STAMP theory and PLS-SEM method - Junjia, Yin; Hizami Alias, Aidi; Azam Haron, Nuzul; Abu Bakar, Nabilah (Institute of Electrical and Electronics Engineers, 2024)
Hoisting is essential for large-scale construction projects, including urban viaducts, high-rise buildings, and undersea tunnels. However, this critical process is subject to frequent safety accidents in China, which result in many casualties and asset losses. The lack of a practical risk framework has contributed to poor safety management in this field. Most of the limited risk frameworks in this field focus only on the direct causes leading to accidents, ignoring the systematic and complex nature of lifting risks. In this study, a new risk framework for lifting is constructed by combining the STAMP (Systems-Theoretic Accident Model and Processes) theory and the quantitative analysis capability of the PLS-SEM (Partial Least Squares Structural Equation Modeling) to effectively identify, assess, and manage various potential risks in the lifting construction process. The factors were then analyzed for importance through the independence weight coefficient method. The study found that 'Failure to conduct pre-operational inspections of lifting equipment and rigging components,' 'Physical or mental impairment of operators, such as intoxication or distraction,' and 'The hoisting program was not prepared under the actual working conditions at the project site and did not adequately plan for emergencies,' were the factors with the top 3 highest weight. Ultimately, the framework is validated by 200 real cases from 2019 to 2024 in China. This proposed STAMP-HC framework can accurately identify the risk transfer paths in accidents, and the results of risk factor weighting can also provide a reference for risk management, with the potential to be extended to other countries.